Biomolecule chitosan, curcumin and ZnO-based antibacterial nanomaterial, via a one-pot process. (1st December 2020) - Karthikeyan, Chandrasekaran; Varaprasad, Kokkarachedu; Akbari-Fakhrabadi, Ali; Hameed, Abdulrahman Syedahamed Haja; Sadiku, Rotimi
Graphical abstract: Highlights: CCZ nanomaterial was prepared by a one-pot precipitation process. Curcumin/chitosan were layered on hexagonal ZnO and the particles are sized ∼48 ± 2 nm. CCZ nanomaterial showed a greater antibacterial effect than the antibiotic amoxicillin. CCZ nanomaterial showed higher anticancer properties against the MCF-7 cells. CCZ nanomaterial is a highly promising material for advanced medical applications. Abstract: As a result of the existence of drug-resistant bacteria and the attendant deficiency of innovative antibiotics, the therapeutic and the clinical sectors are, continually, in search of appropriate multifunctional nanomedicines. Herein, curcumin-chitosan-zinc oxide (CCZ) was successfully synthesized by a one-pot method. Transmission electron micrograph reveals that curcumin and chitosan were layered on a hexagonal ZnO and the particles are sized to ∼48 ± 2 nm. X-ray diffractogram confirmed the formation of CCZ crystal structure. The photoluminescence spectra of CCZ, shows blue and green emissions at 499 nm and 519 nm, respectively, due to the active radicals generated in the nanomaterial, which are responsible for the associated antimicrobial and anticancer activities. The antibacterial activity of the CCZ, performed against methicillin-resistant Staphylococcus aureus (MRSA) and Escherichia coli ( E. coli), showed a greater antibacterial effect than the commercial amoxicillin. The cytotoxic effect of the CCZ nanomaterial was examined in cultured (MCF-7) human breast cancer cells. An IC50 concentration value of 43.53 μg/mL, was recorded when evaluated after 24 h of CCZ with the MCF-7 cell line. From this study, it is believed that CCZ is a highly promising nanomaterial, which will be suitable for advanced clinical applications.